(3bUI SfZGahQIs (3ePcQGJ dj chGf jhs - (3jh, dj chGfs; (3GdOLGfj, gTGes ((3GdQjGVs (3ecJHI GdYHjcGfs, 2007)
(3jSJQLY dj GdeYGQc VO GdGSJYeGQjjf h GdTjhYjjf h GdWGFajjf GdJj bGOJ Edi GSJbdGd SfZGahQIs
1 2 4 10 11 12 13
Keywords: (3GdQLGds -- (3JQGLes; (3GdSjGSjhfs -- (3JQGLes; (3SfZGahQIs -- (3GdCMhGd GdGbJUGOjIs